Effects of oxygen concentration and inlet velocity on pulverized coal MILD combustion. (1st May 2020) - Kuang, Yucheng; He, Boshu; Tong, Wenxiao; Wang, Chaojun; Ying, Zhaoping
Abstract: The inlet velocity is an important parameter in the Moderate or Intense Low-Oxygen Dilution (MILD) combustion. Different inlet velocities not only change the flow of the flue gas, but also affect the dilution effect of the circulating flue gas and the temperature distribution of the furnace. In coal MILD-oxy combustion, different oxygen concentrations change the amount of flue gas and inlet velocity when the excess oxygen coefficient is fixed. Therefore, the change of inlet velocity is worthy of attention in MILD-oxy combustion. In this work, the MILD combustion characteristics with different inlet velocities at different oxygen concentrations are discussed by changing the burner diameter. The results show that increasing the inlet velocity suppresses the temperature peaks in both MILD-air and MILD-oxy combustion. When the inlet velocity is fixed, the flame temperature is increased with the O2 concentration. The facilitation of char gasification reaction with increasing oxygen concentration is also partly due to the increase of temperature and char gasification is also partially affected by the O2 concentration. In terms of heat transfer, the inlet velocity has a large effect on convective heat transfer. Highlights: MILD-oxy coal combustion is studied at several O2 concentrations and velocities. Increased the inlet O2 concentration makes the peak combustion temperature higher. Increasing the inlet velocity can enhance the MILD-oxy coal combustion. The effect of circulated flue gas is more significant on char combustion. The char gasification is greatly affected by temperature and CO2 concentration.